The finance growth link: Comparative analysis of two Eastern African countries - Ashenafi Beyene Fanta; Daniel Makina (Comparative Economic Research. Central and Eastern Europe, 2016)
This paper examines the finance growth link of two low-income Sub-Saharan African economies - Ethiopia and Kenya - which have different financial systems but are located in the same region. Unlike previous studies, we account for the role of non-bank financial intermediaries and formally model the effect of structural breaks caused by policy and market-induced economic events. We used the Vector Autoregressive model (VAR), conducted impulse response analysis and examined variance decomposition. We find that neither the level of financial intermediary development nor the level of stock market development explains economic growth in Kenya. For Ethiopia, which has no stock market, intermediary development is found to be driven by economic growth. Three important inferences can be made from these findings. First, the often reported positive link between finance and growth might be caused by the aggregation of countries at different stages of economic growth and financial development. Second, country-specific economic situations and episodes are important in studying the relationship between financial development and economic growth. Third, there is the possibility that the econometric model employed to test the finance growth link plays a role in the empirical result, as we note that prior studies did not introduce control variables.
Keywords: 330; finance; growth; Ethiopia; Kenya; stock markets; private credit